The long term impacts of grants on poverty: 9-year evidence from Uganda's Youth Opportunities Program - Christopher Blattman; Nathan Fiala; Sebastian Martinez (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
In 2008, Uganda granted hundreds of small groups 400/person to help members start individual skilled trades. Four years on, an experimental evaluation found grants raised earnings by 38% (Blattman, Fiala, Martinez 2014). We return after 9 years to find these start-up grants raised earnings and consumption temporarily only. Grantees' investment leveled off; controls eventually increased their incomes through business and casual labor; and so both groups converged in employment, earnings, and consumption. Grants had lasting impacts on assets, skilled work, and possibly child health, but had little effect on mortality, fertility, health or education.
Keywords: J24; O12; D13; C93; 330; employment; poverty; entrepreneurship; cash transfers; occupational choice; Uganda; field experiment; labor market programs; health; education